PENGARUH INDEKS KEPUASAN MASYARAKAT UNIT PELAYANAN INSTANSI PEMERINTAH KABUPATEN INDRAGIRI HULU - Romagia SE.,M.Si (STIA Indragiri, 2018)
Abstract : To improve the quality of service to the community in Indragiri Hulu , required readiness of the service unit . To find a service unit of service required an assessment that one of them is through public appraisal by the visitors / users of their services by implementing community satisfaction index surveys in several public service units in Indragiri Hulu . Survey of community satisfaction index is expected to give results that is able to trigger a paradigm shift from managing the public service units into units of service that meets the expectations of society.Keyword : Service Unit, Public Service, Expectations of Society, Community Satisfaction